Análisis de riesgos laborales en los laboratorios de la carrera de Agroindustrias de la ESPAM MFL, para mejorar condiciones de seguridad en el personal académico. - Zambrano Cedeño, José Javier (2024)
The present research topic aims to analyze, evaluate, and control occupational risk factors to which academic staff is exposed in the laboratories of Bromatology, Water and Soil, Analytical Chemistry, and Microbiology of the Agroindustries program at the Manuel Félix López Agropecuary Polytechnic School of Manabí. The qualitative-quantitative research method is used for this purpose, as it is a non-experimental study that observes the actual working conditions in these laboratories. These activities will be supported by national and international regulations regarding occupational safety and hygiene. To document the presence of risk factors, the qualitative method will be used to identify them through the use of a risk matrix. Additionally, the levels at which these factors are found will be analyzed, and control measures to be implemented will be determined. Surveys will be used as a field instrument to quantitatively track the progress of the method. It is also important to mention the use of documentary, field, and observational bibliography. Based on the obtained results, a manual for occupational risks will be developed. This manual will serve as a guide to implement the necessary control measures for this type of risk, allowing the Higher Education Institution to comply with current regulations related to industrial safety and occupational health within the laboratories.